2017
DOI: 10.1007/s11356-016-8341-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, spatial distribution, and ecological risks of typical hydroxylated polybrominated diphenyl ethers in surface sediments from a large freshwater lake of China

Abstract: Hydroxylated polybrominated diphenyl ethers (OH-PBDEs) have been frequently observed in marine aquatic environments; however, little information is available on the occurrence of these compounds in freshwater aquatic environments, including freshwater lakes. In this study, we investigated the occurrence and spatial distribution of typical OH-PBDEs, including 2'-OH-BDE-68, 3-OH-BDE-47, 5-OH-BDE-47, and 6-OH-BDE-47 in surface sediments of Taihu Lake. 3-OH-BDE-47 was the predominant congener, followed by 5-OH-BDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…48 Previous studies have reported that the TOC appears to play a key role in controlling the distribution of OH-PBDEs and MeO-PBDEs, and significant positive correlations were observed between metabolites concentrations and TOC contents in marine sediments. 49,50 The TOC content of Antarctic sediments (3.3%) was higher than that of Arctic sediments (0.20−1.3%), and a significant positive correlation was observed between metabolite concentrations and organic carbon contents in Arctic sediments (p < 0.05). To minimize the effect of sediment organic matter contents on contamination levels, the total concentrations in the sediment in Figure 1 were expressed on a TOC weight (TOC w) basis as well.…”
Section: Resultsmentioning
confidence: 99%
“…48 Previous studies have reported that the TOC appears to play a key role in controlling the distribution of OH-PBDEs and MeO-PBDEs, and significant positive correlations were observed between metabolites concentrations and TOC contents in marine sediments. 49,50 The TOC content of Antarctic sediments (3.3%) was higher than that of Arctic sediments (0.20−1.3%), and a significant positive correlation was observed between metabolite concentrations and organic carbon contents in Arctic sediments (p < 0.05). To minimize the effect of sediment organic matter contents on contamination levels, the total concentrations in the sediment in Figure 1 were expressed on a TOC weight (TOC w) basis as well.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxylated BDE‐47, especially 6‐OH‐BDE‐47, usually found to be the dominant congener in various types of matrixes (Lacorte, Ikonomou, & Fischer, 2010; Ren et al, 2013; Fan et al, 2014a,b; Lindqvist & Asplund, 2019). In addition, 3‐OH‐BDE‐47, 5‐OH‐BDE‐47, 6‐OH‐BDE‐47, and 2′‐OH‐BDE‐68 usually have relatively higher concentrations in biotic and abiotic samples and attracted more attention (Zota et al, 2011; Eguchi et al, 2012; Haraguchi et al, 2016; Liu et al, 2017).…”
Section: Distribution Of Oh‐pbdesmentioning
confidence: 99%
“…Though the investigated OH‐PBDE species and trimester of pregnancy were different, Zota et al (2011) got similar results that TSH had positive associations with OH‐PBDEs, but the relationship between OH‐PBDEs and T4 was weak. A cohort study with 33 thyroid cancer patients found that lg∑OH‐PBDEs were positively associated with lgTSH, while lg3‐OH‐BDE‐47 inversely associated with lgFT (free T4) and lg4′‐OH‐BDE‐49 positively associated with TSH (lg… represents the concentrations were compared after logarithmic transformation) (Liu et al, 2017). In consideration of the negative feedback regulation of thyroxines on TSH, these results support the view that OH‐PBDEs influence thyroid functions through eliminating serum thyroxine with elevating TSH levels.…”
Section: Toxicitymentioning
confidence: 99%
“…In fish tissues sampled from the Detroit River between US and Canada, the concentrations of 6-OH-BDE-47 ranged between 1.5 and 10 pg/g (wet weight) (Valters et al, 2005). In surface sediment samples from freshwater Taihu Lake in China, the concentrations of 6-OH-BDE-47 ranged between <0.1 and 0.350 ng/g (dry weight) (Liu et al, 2017). In the laboratory, it induced developmental arrest in zebrafish embryos (Danio rerio) in a concentration-dependent manner (Usenko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%